Tethered swimming as an estimator of anaerobic capacity - Morouco, P.; Neiva, H.; Marinho, D.; Marques, M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Relationships between tethered swimming (TS) and swimming performance have been previously studied. Nevertheless, most of these approaches studied heterogeneous groups. West et al. (2005) stated that to remain stationary, the swimmer relies mostly on fast glycolytic muscle fibers increasing the production of lactic acid. This was not verified in a recent study, reinforcing the importance of more studies under this scope. Methods: 3 homogeneous groups (variation of Personal Best 100-m Free < 2.5%) of 8 male swimmers (G1: 13.0±0.7y-of-age, 54.5±3.9kg, 164.8±6.8cm; G2:14.9±0.6y-of-age, 60.7±6.9kg, 172.1±6.6cm; G3: 19.9±1.7y-of-age, 75.6±7.6kg, 180.6±10.4cm) took part in the study. Maximum 30-s front crawl TS assessed maximum (Fmax) and mean force (Fmean). One day after, subjects performed 2 maximal front crawl swims (FS) with an underwater start (100- and 50-m) to obtain swimming velocity (v100 and v50). Blood samples from earlobe were taken after warm-up and at the terminus of the tests allowing the estimation of ä[La-]. After Shapiro-Wilk normality test, parametric procedures were applied. The statistical significance was set at p<0.05. Results: TS variables were higher in G3 than G2, than G1 (Fmax - 316.7±27.3N > 260.7±27.4N > 221.8±19.9N, p<0.05; Fmean - 126.6±10.9N > 102.9±11.3N > 93.9±12.1N, p<0.001). In ä[La-] higher differences were obtained between TS with 100-m (p<0.0001) than with 50-m FS (p<0.05). Fmax presented a high correlation with v50 in G3 (r=0.87, p<0.001). In G2 relationships were observed between v50 with Fmax (r=0.77, p<0.001) and Fmean (r=0.73, p<0.05). Fmean correlated significantly with v50 (r=0.63, p<0.05) and v100 (r=0.68, p<0.05) for G1. ä[La-] presented moderate to high (r=0.55-0.86) correlations both with TS values and FS velocities. Discussion: As expected upper level swimmers presented superior values of force exerted in water, corroborating the validity of the methodology used. In groups alike, ä[La-] in TS did not exceed the values of FS, contrasting the statement of West et al. (2005). For the different groups, correlations between force parameters and performance were estimated and differ according to age, force parameter and distance swam. These data could corroborate the idea that TS may be useful to discern between "sprinters" and "distance" swimmers profiles. The associations between ä[La-] with force exerted in water and swimming velocities support the idea that the capacity to obtain higher values of force production and swimming velocities, is related with an enhanced production of energy through the glycolytic system. Our data suggest that TS may be useful to monitor and evaluate anaerobic training.